2015
DOI: 10.1080/0361073x.2015.1021644
|View full text |Cite
|
Sign up to set email alerts
|

Negative Arousal Increases the Effects of Stimulus Salience in Older Adults

Abstract: Background/Study Context Stimuli compete for mental representation, with salient stimuli attracting more attention than less salient stimuli. In a recent study, we found that presenting an emotionally negative arousing sound before briefly showing an array of letters with different levels of salience increased the reporting of the more salient letters but decreased reporting of the less salient letters (Sutherland & Mather, 2012). In the current study we examined whether negative arousal produces similar effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
0
22
2
Order By: Relevance
“…Priority in the competition is determined by both bottom-up perceptual saliency (e.g., stimuli that move suddenly or are brighter than their surroundings; Itti et al, 1998 ) and top-down goal-relevancy (e.g., finding a friend in a crowd; Beck and Kastner, 2009 ). Consistent with ABC, recent studies have demonstrated that emotional arousal facilitates subsequent perception of non-emotional, visually salient stimuli, while impairing perception of non-salient stimuli ( Lee et al, 2012 , 2014b ; Sutherland and Mather, 2012 , 2015 ).…”
Section: Introductionmentioning
confidence: 64%
“…Priority in the competition is determined by both bottom-up perceptual saliency (e.g., stimuli that move suddenly or are brighter than their surroundings; Itti et al, 1998 ) and top-down goal-relevancy (e.g., finding a friend in a crowd; Beck and Kastner, 2009 ). Consistent with ABC, recent studies have demonstrated that emotional arousal facilitates subsequent perception of non-emotional, visually salient stimuli, while impairing perception of non-salient stimuli ( Lee et al, 2012 , 2014b ; Sutherland and Mather, 2012 , 2015 ).…”
Section: Introductionmentioning
confidence: 64%
“…Then, we ran the same analysis on the data of 55 participants from an ageing population (61-80 years old; Sutherland & Mather, 2015). The data from one participant were discarded due to extreme weights, which were more than 7 standard deviations from the group mean in one of the conditions.…”
Section: Discussionmentioning
confidence: 99%
“…All participants reported having normal or corrected-to-normal vision and hearing. We based our sample size on previous studies using this paradigm (Sutherland & Mather, 2015, 2012)…”
Section: Methodsmentioning
confidence: 99%